Variability of sea ice melt and meteoric water input in the surface Labrador Current off Newfoundland - Benetti, M; Reverdin, G; Pierre, C; Khatiwala, S; al., E (American Geophysical Union, 2016)
The respective contributions of saline (Atlantic and Pacific water) and freshwater (sea ice melt, meteoric water) components in the surface Labrador Current are quantified using salinity, δ18O, and nutrient data collected between 2012 and 2015 east of Newfoundland to investigate the seasonal variability of salinity in relation with the different freshwater contributions. Nutrient data indicate that the surface saline water is composed on average over 2012-2015 of roughly 62% Atlantic Water and 38% Pacific Water. A large salinity seasonal cycle of ≈ 1.5 peak-to-peak amplitude is found over the middle continental shelf, which is explained by the freshwater input seasonal variability: 2/3 of the amplitude of the salinity seasonal cycle can be explained by meteoric water input and 1/3 by the sea ice melt. A smaller seasonal salinity cycle (≈1.3) is observed over the inner shelf compared to the middle shelf, because of smaller variability in the large meteoric water inputs. Furthermore, the data reveal that sea ice melt (SIM) input was particularly important during July 2014, following a larger extension of sea ice over the Labrador shelf during the 2013/2014 winter season, compared to both previous winter seasons. Some patches of large SIM contribution observed during July 2014 and April 2015 were located on the continental slope or further offshore. The comparison of 2012-2015 data with data collected in 1994-1995 shows that the surface water over the Newfoundland shelf and slope is strongly affected by sea ice processes in both periods and suggests a larger contribution of brines over the slope during 1994-1995.